The Relationship of Information Technology, School Environment, Emotional Intelligence, and Intellectual Intelligence on the Learning Achievement of Students - Putra, Rio Andhika; Candana, Dori Mittra (UPI YPTK Journal of Business and Economics, 2024)
This research aims to determine how much influence Information Technology, School Environment, Emotional Intelligence, and Intellectual Intelligence have on the Learning Achievement of Students at SMK Negeri 9 Padang. The research results obtained were (a) that there was no significant influence of the Information Technology variable on the learning achievement of students at SMK Negeri 9 Padang, (b) there is a positive and significant influence of the School Environment variable on the Learning Achievement of students at SMK Negeri 9 Padang (c) there is a positive and significant influence of the Emotional Intelligence variable on the Learning Achievement of SMK Negeri 9 Padang students (d) there is no significant influence of the Intellectual Intelligence variable on the Learning Achievement (e) Simultaneously there is a significant influence between Information Technology, School Environment, Emotional Intelligence and Intellectual Intelligence on Student Learning Achievement